MEMBONGKAR KESALAHAN POLA ASUH ANAK DALAM MITOS-MITOS DI INDONESIA - Liliani, Else (Diksi, 2008)
This article is about a research conducted to clarify (1) the structuralcharacteristics of myths in Indonesia, (2) the child-rearing patterns found in themyths, (3) errors in child rearing reflected in the myths, and (4) the relevance of themyths and child-rearing patterns to the contemporary realities in Indonesia.With the myths in Indonesia as the objects of the research, by means ofpurposive random sampling, 15 myths were selected for study. The data wereobtained by means of a read-and-write technique and they were analyzed by (1)reading the myths and seeking the story units and (2) organizing the story units inaccordance with the story development. The validity of the data was tested throughsemantic validity and their reliability was tested by repeated readings.The research results indicate that (1) the structural characteristics of mythsin Indonesia are, among others, that (a) in child rearing the mother figures have thecharacteristic of being gentle and a part of the father figures have the characteristicof being stern, (b) most of the myths have the social background of the lower classand the economic background of the poor, (c) the child figures possess asufficiently good need of achievement and a sufficiently good emotional quotient,(d) the child figures experience considerable social conflict, (e) the parent figuresplay minimum parts in the story, and (f) most of the child figures receivepunishments and experience dehumanization, (2) the patterns of child rearing arefound to have enough variety but they are mostly dominated by authoritarian,neglectful, and indulgent ones, (3) the errors of child rearing reflected are, amongothers, the minimum roles of parents and a disproportional child-rearing pattern ofgiving more punishments than rewards, and (4) the myths put under study haverelevance to today's matters related to child rearing such as education, health, andchild abuse.Keywords: myths, structure and pattern of child rearing